2019
DOI: 10.1097/md.0000000000016151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of warmed humidified carbon dioxide insufflation in infants undergoing major laparoscopic surgery

Abstract: Purpose: Some studies have reported that warmed humidified carbon dioxide (CO 2 ) insufflation in adult laparoscopic surgery could reduce pain and improve the core body temperature (CBT). However, similar studies are lacking in infants. Thus, this study aimed to investigate the clinical effects of warmed, humidified CO 2 insufflation in pediatric patients undergoing major laparoscopic surgeries. Methods: From January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Last but not least, a study conducted on pediatric patients who had undergone laparoscopic surgery demonstrated that heated and humidified CO2 insufflation better maintained the internal temperature than standard CO2 insufflation. They also propounded positive postoperative outcomes, such as reduced shivering and shorter hospital stays for patients [ 9 , 17 ]. Of note, pediatric cases face more significant challenges in maintaining their body temperature and are at a higher risk of hypothermia compared to adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, a study conducted on pediatric patients who had undergone laparoscopic surgery demonstrated that heated and humidified CO2 insufflation better maintained the internal temperature than standard CO2 insufflation. They also propounded positive postoperative outcomes, such as reduced shivering and shorter hospital stays for patients [ 9 , 17 ]. Of note, pediatric cases face more significant challenges in maintaining their body temperature and are at a higher risk of hypothermia compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations in temperature due to carbon dioxide (CO2) insufflation during laparoscopic surgeries appear [2][3][4][5][6]. In addition, warming and humidification of insufflated CO2 gas have been reported in order to reduce the development of hypothermia [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Two articles (11,26) compared the performance of a surgical procedure in different environments (Operating Room (OR) and Neonatal Intensive Care Unit (NICU)) and evaluated where there was a higher incidence of hypothermia in the NBs; another (25) analyzes the OR temperature and correlates it with small and large surgeries and, finally, investigates (24) the necessary strategies to provide the ideal surgical environment for maintaining normothermia in NBs. It is stipulated as thermal parameters of a neonatal operating room: room temperature with a variation of 22.7ºC to 28ºC (11,15,(24)(25)(26)(31)(32) , air humidity control between 32% and 62% (24)(25)(26)32) and quality of air cleaning, based on the International Standardization Organization (ISO) 14644-1 with numerical classes (26) .…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese hospitals, other strategies have been shown to be effective, namely: heated and humidified CO 2 insufflation (35°C temperature and 95% relative humidity) in laparoscopic surgeries (32) ; rewarming of children with postoperative hypothermia with the combination of an electric blanket and a forced air heating system (34) . These resources were associated with positive postoperative results, including less tremors and hypothermia, faster recovery of bowel movements and shorter hospital stay (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the peritoneal cavity milieu at physiological conditions may minimize unwarranted peritoneal tissue injury thereby reducing postoperative complications. Warm humidified CO 2 (WHCO 2 ) insufflation in laparoscopic procedures has shown promise, albeit in small uncontrolled studies, in maintaining normothermia, reducing postoperative pain, time to first bowel motion and length of stay [7,9,10]. However, study results are varied, making it difficult to draw definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%